How do I solve

(1/8) * (4 1/2) * + (3/8) * (4 1/2) + (4 1/2) * (1/2)

2 answers

To solve this expression, we first need to convert the mixed number 4 1/2 into an improper fraction, which would be (9/2). Then we can simplify the expression:

(1/8) * (9/2) + (3/8) * (9/2) + (9/2) * (1/2)
= (9/16) + (27/16) + (9/4) (I multiplied the numerators first, then the denominators second)
= (9/16) + (27/16) + (36/16)
= 72/16
= 9/2

Therefore, the answer is 9/2 or 4 1/2.
impatient much?
Once is enough, thank you.
Repeated postings will not get faster or better responses.